The Role of the Social Model in Increasing Regional Competitiveness - Dužinskas, Raimundas; Svirbutaitė-Krutkienė, Giedrė (Socialiniai tyrimai, 2018)
Although the regional competitiveness is essentially related to its economic activity, there is an increasing consensus that competitiveness is best assessed in the context of regional business environment assets such as human capital, innovative capacity, local infrastructure quality, etc. (Huggins, Izushi, Prokop, Thopson, 2014). Thus, the regional competitiveness is not only economic indicators, it is increasingly based on creativity, knowledge and environmental conditions. Competitiveness is a multidimensional term, so soft variables need to be taken into account in order to understand, assess and strengthen regional activity and development. Therefore the purpose of this article is to determine the role of the social model to the increase of the regional competitiveness (Borozan, 2008). The aim of the article is to determine the role of the social model in increasing the competitiveness of the region. In order to achieve the goal, the following objectives are formulated: to analyze social models by identifying their characteristics; to assess the suitability of selected social models for the increase of regional competitiveness; to analyze and evaluate the regional policy in Lithuania. The main methods used are scientific literature analysis, statistical analysis, expert evaluation, descriptive analytical and comparative analysis. The first typology of welfare states models was presented by English political scientist R.Titmuss, who distinguishes three models – marginal (residual) model, which is found in United States and means that the main function of welfare providers lies with the market and family; industrial achievement performance model in Germany based on the level of industry in a country, where the welfare depends and is closely linked to work and productivity; and the institutional-redistributive model usually applied in Scandinavian countries, in which the provision of welfare depends on needs. Subsequently, Danish sociologist G.Esping-Andersen adjusted the classification of social models develop ed by R.Titmuss by adapting it more to the political science, thus identifying three welfare state regimes (models) - liberal, conservative-corporate and social-democratic (redistributive) (Aidukaitė, 2010). These three models differ in the aspects of the organization of social policy, their dependence on the market conditions, their ideology, priorities, the impact on the country’s stratification system, which means the division of society into social strata and the degree of decommodification, defining the person’s liberation from the need to work while maintaining the basic standards of life (material life conditions). Some states quite clearly reflect the typology of G. Esping-Andersen. For example, Germany is an example of a conservative-corporate model, Norway or Sweden is a social-democratic model, while a liberal model is typically found in Anglo-Saxon states. However, there are many states with certain characteristics that are inherent different kind of welfare systems (models). Therefore, in different scientific research the place in the typology of some countries differs because researchers tend to emphasize a particular feature or characteristic that determines the assignment of a state to different types. This article proves, that in order to review the diversity of the whole world, three models are not enough. Given that none of these models do not exist in a pure form. Taking this into account, the main attempts to extend or to adjust the essentially considered as traditional typology by E. Esping-Andersen are presented in this article. Most of such attempts are limited to extending the typology by inserting a fourth or several additional types (models), for example, southern model, Latin region model, European Union model, post-communist states model, etc. As mentioned before, there is a large variety of social models in the world, although only three are considered as main models – liberal (in Anglo-Saxon countries), conservative (in Scandinavian countries) and social-democratic (originating from Germany). In order to determine which one of these three models may be the most competitive in the globalized economy Regional Competitiveness Index published by the European Commission has been analyzed. Regional competitiveness is understood as the ability of a region to offer an attractive and sustainable environment for firms and residents to live and work. The Regional Competitiveness Index consists of eleven indicators (pillars), divided into three groups (dimensions): basic dimension, efficiency dimension and innovation dimension. The Global Competitiveness Report, published by the World Economic Forum, was also detailed analyzed. The countries representing different social models were studied: United States and United Kingdom representing the liberal model, Scandinavian countries (Sweden, Finland, Denmark and Norway) representing the social-democratic model and Germany representing the conservative model. The research has shown that countries with a liberal social model, compared with other models, have achieved better results in assessing their competitiveness. The particular attention is paid to the case of Lithuania – the social model as well as the development of regional policy in Lithuania have been analyzed with special focus on the decision to divide Lithuania into two regions. Having assessed all the circumstances, it is not yet clear whether the solution of division of Lithuania into two regions can be justified. Such decision was made without proper modeling of socio-economic consequences of the corresponding process. The division of Lithuania into two regions would inevitably mean greater concentration of the population in one, in economic and social sense stronger, more business-intensive and more innovative region. Therefore, the chosen decision of the division of the two regions into Lithuania can not be scientifically considered as unquestionable, consequently more detailed research is needed in order to model the consequences of such an administrative division.